Advanced design of a small-scale mini gerotor pump in a high-temperature and high-viscosity fluid thermal system - Zariatin, Dede Lia; Suwandi, Agri (Eastern-European Journal of Enterprise Technologies, 2023)
In this research, the development of a small-scale heat transfer gerotor pump with an advanced arrangement for high-viscosity and high-temperature fluids is described comprehensively. The small-scale pump design aims to meet the needs of modular components for industry and research, especially for small-scale heat transfer applications such as residential heating systems. VDI 2221 approach was used to construct an advanced gerotor pump with an internal reservoir unit that can generate additional pressure and minimize the slip factor, thereby increasing its volumetric efficiency. The developed small-scale pump was designed in a smart arrangement, which required fewer components than a typical heat transfer pump. This helps to reduce the maintenance of the pump and its components. Experimental tests were performed using a testing apparatus equipped with a heater, a control system using Pulse Width Modulation (PWM) adjustment, valves, pressure, and temperature gauges. The instruments in the apparatus test were used to control the flow rate and pump speed and monitor the temperature of the working fluid. The results of the experiment show that the advanced gerotor pump was able to deliver fluid with a viscosity of 307 ml/min and a temperature of up to 230 °C. The components arrangement minimizes the slip factor, which is mostly the main challenge of positive displacement pumps. The maximum slip coefficient of the advanced gerotor pump design is 0.095. The volumetric efficiency was in the range of 0.803–0.905 when the pump operated at 2,100 RPM and 230 °C. The experiment and analysis results show that the pump can be implemented for the actual application of the thermal system, for research and industry